2007
DOI: 10.1021/tx6003387
|View full text |Cite
|
Sign up to set email alerts
|

DC-81-Indole Conjugate Agent Induces Mitochondria Mediated Apoptosis in Human Melanoma A375 Cells

Abstract: DC-81, an antitumor antibiotic produced by the Streptomyces species, belongs to pyrrolo[2,1-c] [1,4]benzodiazepine (PBD), which are potent inhibitors of nucleic acid synthesis. We previously reported an efficient synthesis of PBD hybrids linked with indole carboxylates. This is the first demonstration on the mechanism of the anticancer effect of PBD hybrid (IN6CPBD) agent on human melanoma A375 cells. IN6CPBD-treated cells exhibited higher cytotoxicity than DC-81 and displayed several features of apoptosis, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Disruption of mitochondrial functions due to oxidative stress factors stimulates the caspase pathway, triggering apoptosis [29]. Also, the stimulation of cells by apoptotic factors facilitates dissociation of the original Bax and Bcl-2, causing an increase in Bax and decrease in Bcl-2 [30]. In this study, we demonstrated that Bcl-2 was markedly suppressed, while Bax and cleaved caspase 3 were increased in the ONFH group.…”
Section: Discussionsupporting
confidence: 47%
“…Disruption of mitochondrial functions due to oxidative stress factors stimulates the caspase pathway, triggering apoptosis [29]. Also, the stimulation of cells by apoptotic factors facilitates dissociation of the original Bax and Bcl-2, causing an increase in Bax and decrease in Bcl-2 [30]. In this study, we demonstrated that Bcl-2 was markedly suppressed, while Bax and cleaved caspase 3 were increased in the ONFH group.…”
Section: Discussionsupporting
confidence: 47%
“…Cells were harvested with trypsin-EDTA and fixed with ice cold 70 % EtOH at 4 8C for 30 min, then the EtOH was removed by centrifugation, and cells were stained with 1 mL of DNA staining solution (0.2 mg of propidium iodide (PI) and 2 mg RNase A) for 30 min as previously described. [28] The DNA contents of 20 000 events were measured by flow cytometry (BD FACSCanto II). Histograms were analyzed using BD FACS Diva software.…”
Section: Biologymentioning
confidence: 99%
“…Induction of apoptosis through the mitochondrial pathway is a strategy for treating melanomas [4]. Alternative activations of Bcl-2 family proteins, including anti-and pro-apoptotic proteins, participate in the apoptotic mitochondrial pathway.…”
Section: Introductionmentioning
confidence: 99%